Glocal Pharma (2021)
The Open Access version of this book, available at http://www.tandfebooks.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. An exploration of how global pharmaceutical products are localized - of what happens when they become ‘glocal’ - this book examines the tensions that exist between a global pharmaceutical market and the locally bounded discourses and regulations encountered as markets are created for new drugs in particular contexts. Employing the case study of the emergence, representation and regulation of Viagra in the Swedish market, Glocal Pharma offers analyses of commercial material, medical discourses and legal documents to show how a Swedish, Viagra-consuming subject has been constructed in relation to the drug and how Viagra is imagined in relation to the Swedish man. Engaging with debates about pharmaceuticalization, the authors consider the ways in which new identities are created around drugs, the redefinition of health problems as sites of pharmaceutical treatment and changes in practices of governance to reflect the entrance of pharmaceuticals to the market. With attention to ‘local’ contexts, it reveals elements in the nexus of pharmaceutcalization that are receptive to cultural elements as new products become embedded in local markets. An empirically informed study of the the ways in which the presence of a drug can alter the concept of a disease and its treatment, understandings of who suffers from it and how to cure it - both locally and internationally - this book will appeal to scholars of sociology and science and technology studies with interests in globalization, pharmaceuticals, gender and the sociology of medicine.